Clinical profile of primary biliary cirrhosis with features of autoimmune hepatitis: Importance of corticosteroid therapy. Issue 9 (19th August 2013) - Yoshioka, Youko; Taniai, Makiko; Hashimoto, Etsuko; Haruta, Ikuko; Shiratori, Keiko
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to elucidate the clinical and histological features, response to corticosteroid therapy and long‐term outcome of primary biliary cirrhosis (PBC) with features of autoimmune hepatitis (AIH). Methods Among 280 PBC patients under ursodeoxycholic acid administration, we identified 28 patients with AIH features fulfilling the following criteria: sustained high levels of serum aminotransferases and high immunoglobulin G levels with positivity for antinuclear antibodies or anti‐smooth muscle antibodies (ASMA) and/or histological features of moderate to severe interface hepatitis or moderate to severe lobular hepatitis. We analyzed PBC patients with AIH features, focusing mainly on therapeutic responses to corticosteroids. Results Patients with PBC with AIH features included 26 women (93%). Their median age was 55 years, and the median follow‐up period was 7.5 years. Eight of these 28 patients were not actually treated with corticosteroids due to medical conditions. Among the 20 patients receiving corticosteroid therapy, 15 were responders and five were non‐responders. A high alkaline phosphatase (ALP) level, negativity for ASMA and positivity for gp210 were identified as risk factors for lack of a response to corticosteroid therapy. Among 28 PBC patients with AIH features, the responders to corticosteroids had an excellent prognosis, while those who could not be treated with corticosteroids and non‐responders to corticosteroids had a poor outcome. Conclusion Patients with PBC with AIH features benefit from corticosteroid therapy. Features of PBC such as high ALP level, negativity for ASMA and positivity for gp210 appear to predict a poor response to corticosteroids.